Seaweeds fast EDC bioremediation: Supporting evidence of EE2 and BPA degradation by the red seaweed Gracilaria sp., and a proposed model for the remedy of marine-borne phenol pollutants. (1st June 2021) - Astrahan, Peleg; Korzen, Leor; Khanin, Marina; Sharoni, Yoav; Israel, Álvaro
Abstract: In the last few decades, Endocrine Disrupting Chemicals (EDCs) have taken significant roles in creating harmful effects to aquatic organisms. Many proposed treatment applications are time consuming, expensive and focus mainly on waste water treatment plants (WWTP), which are indeed a major aquatic polluting source. Nonetheless, the marine environment is the ultimate sink of many pollutants, e.g. EDCs, and has been largely neglected mainly due to the challenge in treating such salty and immense open natural ecosystems. In this study we describe the bromination and the yet unpresented degradation process of high concentrations (5 mg/L) of phenolic EDCs, by the marine red macroalgae Gracilaria sp. As shown, 17α-Ethinylestradiol (EE2), a well-known contraceptive drug, and one of the most persistent phenol EDCs in the environment, was eliminated from both the medium and tissues of the macroalga, in addition to the degradation of all metabolites as verified by the nil estrogenic activity recorded in the medium. Validation of the proposed bromination-degradation route was reinforced by identifying Bisphenol A (BPA) brominated degradation products only, following 168H of incubation in the presence of Gracilaria sp. As demonstrated in this assay for EE2, BPA and finally for paracetamol, it is likely that the phenol scavenging activity is nonspecific and, thus, possibly even a wider scope of various other phenol-based pollutants might be treated in coastal waters. As far as we know, Gracilaria sp. is the only marine sessile organism able of degrading various phenol based pollutants. The worldwide distribution of many Gracilaria species and their wide aquaculture knowhow, suggest that bioremediation based on these seaweeds is a possible cost effective progressive solution to the treatment of a wide scope of phenols at the marine environment. Graphical abstract: Image 1 Highlights: EE2, BPA and paracetamol were brominated by the red macroalgae Gracilaria sp. EE2 estrogenic nil activity and BPA brominated degradation products were recorded. EE2 and BPA degradation was recorded in incubation studies. Gracilaria sp. mediated bromination, is suspected as a degradation perquisite. Gracilaria sp. may be used as a cost effective EDCs remedy in marine environments. Abstract : Gracilaria sp. showed a fast bromination step, followed by a degradation process of phenolic EDCs. The degradation process was rather unspecific, yet in different time rates.